A phytobiotic extract, in an aqueous or in a cyclodextrin encapsulated form, added in diet affects meat oxidation, cellular responses and intestinal morphometry and microbiota of broilers - Dokou, Stella; Mellidou, Ifigeneia; Savvidou, Soumela; Stylianaki, Ioanna; Panteli, Nikolas; Antonopoulou, Efthimia; Wang, Jing; Grigoriadou, Katerina; Tzora, Athina; Jin, Lizhi; Skoufos, Ioannis A.; Giannenas, Ilias (Frontiers in Animal Science, 2023)
The present trial examined the effects of diet supplementation with an extract including Greek oregano, garlic, rock samphire, and camelina, administered either in aqueous form or encapsulated in cyclodextrin, on broiler chickens. The duration of the trial was 35 days. Mixed broiler chicks (Ross-308, 120 individuals, 1 day old) were randomly allocated to one of three groups, each with four replicates. Control group A (CONTROL) was fed a basal diet consisting of maize and soybean. The diet of the AQORGCC and CDORGCC groups was further supplemented with aqueous and cyclodextrin-encapsulated herbal extracts, respectively. Levels of lipid and protein oxidation were determined in breast and thigh meat samples. Furthermore, to address cellular stress and signaling responses, the expression patterns of heat shock proteins (Hsp60, Hsp70, and Hsp90), mitogen-activated protein kinases (P38 and P44/42 MAPKs), and apoptotic-related proteins (Bcl-2/Bad ratio) were investigated in breast and thigh tissues using Western blot analysis. The intestinal morphometry of the duodenum, jejunum, and ileum was also assessed. To investigate ileal and cecal bacterial community diversity, 16S rRNA gene high-throughput amplicon sequencing on the V3–V4 hypervariable region was performed. The results showed that the herbal extract in cyclodextrin delayed meat lipid oxidation. According to the protein expression patterns, the formulated diets elicited tissue-specific cellular responses. Compared with the CONTROL group, dietary supplementation with the encapsulated form resulted in significant Hsp induction and MAPK activation, whereas, in the group whose diet was supplemented with the aqueous form, the expression of most of the examined proteins decreased or was maintained at a constant level. Villus height and lamina propria width were mostly affected by the aqueous herbal extract, whereas the number of goblet cells remained unchanged among the groups. Firmicutes, Proteobacteria, and Bacteroidota were the major phyla in mean relative abundance in all diets in both cecal and ileal samples. Alpha-diversity indices highlighted higher species richness and diversity in the cecum than in the ileum, as well as in chicks treated with the aqueous extract of the herbal mixture, but only in the cecum. Cecal beta-diversity differed between the cyclodextrin and the CONTROL groups, while ileal beta-diversity varied only between the aqueous-treated group and the CONTROL group. In conclusion, the dietary mixtures of herbal extracts (particularly those encapsulated in cyclodextrin) improved protein and lipid oxidation and increased the number of beneficial lactic acid-producing bacteria in the cecum, whereas the aqueous herbal extract mostly affected bacterial activity in the proximal part of the chicken intestine. Similarly, intestinal morphometry in the duodenum, jejunum, and ileum was mostly affected by the aqueous herbal extract, which seems to inhibit proteins associated with stress signaling in meat.